2014
DOI: 10.1111/meca.12053
|View full text |Cite
|
Sign up to set email alerts
|

Growth with Unused Capacity and Endogenous Capital Depreciation

Abstract: The paper contributes to the debate on growth and distribution in a non‐mainstream perspective. It looks at the role that capacity utilization plays in the process of growth under the hypothesis that the rate of capital depreciation is a function of the degree of capacity utilization. Our hypothesis implies results partly different from those obtained by other models in which capacity utilization plays a key role. In particular, a varying rate of depreciation affects the conditions under which distributional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The Bhaduri-Marglin investment function can be thought of as weakening the "strong" accelerator effect characteristic of the canonical Kaleckian investment function(Blecker, 2002, p.135).3 See, for example, the dissenting views ofMott and Slattery (1994).4 Some of these results were contemporaneous with those ofMarglin and Bhaduri (1990) andBhaduri and Marglin (1990) -see especiallyBlecker (1989), who showed that international price competition increases the possibility of a profit-led regime. The identification of new influences on the wage-or profit-led character of the growth process continues: see, for example,Patriarca and Sardoni (2014), who identify the rate of depreciation as affecting the response of growth to redistributions of income.5 Consumption-driven, profit-led growth is one example of a general class of growth regimes that Hein and Dodig (2014), followingCordonnier (2006), term "profits without investment" regimes.…”
mentioning
confidence: 99%
“…The Bhaduri-Marglin investment function can be thought of as weakening the "strong" accelerator effect characteristic of the canonical Kaleckian investment function(Blecker, 2002, p.135).3 See, for example, the dissenting views ofMott and Slattery (1994).4 Some of these results were contemporaneous with those ofMarglin and Bhaduri (1990) andBhaduri and Marglin (1990) -see especiallyBlecker (1989), who showed that international price competition increases the possibility of a profit-led regime. The identification of new influences on the wage-or profit-led character of the growth process continues: see, for example,Patriarca and Sardoni (2014), who identify the rate of depreciation as affecting the response of growth to redistributions of income.5 Consumption-driven, profit-led growth is one example of a general class of growth regimes that Hein and Dodig (2014), followingCordonnier (2006), term "profits without investment" regimes.…”
mentioning
confidence: 99%